The Effect of Work From Anywhere Patterns on Employee Motivation and Performance - Desy Tri Anggarini; Andang Prihasnowo (Jurnal Inovasi Bisnis dan Kewirausahaan, 2023)
The Covid pandemic in 2020 has had an extraordinary impact. Communities must make adjustments in carrying out their daily activities, including adaptation to new work patterns. As a form of transformation, the Ministry of Finance changed the work pattern from the beginning of working in an office to a Work From Anywhere (WFA) pattern. The WFA work pattern combines several work patterns, namely, working in an office, a satellite office, and working from home. Everyone works based on different motivations and is determined by various internal and external factors. Internal factors include boredom, the desire to gather with co-workers, and happiness with family. The external factor is the availability of working facilities in the office, at a satellite office, or when working from home. Employee performance has a significant influence on organizational performance. Organizational goals will be achieved if there is support from employees in the form of completing tasks assigned to employees. This study aimed to determine the effect of WFA work patterns on employee Motivation and performance. The research method used is descriptive qualitative. The data is processed based on a questionnaire from 26 respondents. The results showed that most respondents agreed with the WFA work pattern and that there was an increase in employee performance (91%) and employee motivation (91%). For work preference, most of the respondents chose to work in a hybrid manner (56%), namely working part of the time in the office and part of the time working from home, by choosing two days to work from home (48%) and choosing a working schedule for 8 hours effective at intervals 08.00- 17.30 (60 %).